Real time B-Scan evaluation of Posterior chamber & extraocular pathologies of Eye & Orbit - singh Netam, Satya bhuwan; Jain, Vishal; Singh, Rajesh; Kumar, Sanjay; Dutt, Vishnu; Singh, Rajesh (International Journal of Medical Research and Review, 2015)
Objective: Aim of this study is to assess the usefulness and accuracy of high frequency real time ultrasound using non dedicated all purpose scanner to detect and characterise posterior chamber and extraocular pathologies in trauma and non-traumatic eye and to establish etiology of proptosis. Material & Method: A total number of 138 cases (145 eyes) were included in the study. Ultrasound evaluation of eyes with diagnosed or suspected posterior segment pathology, cases of trauma, suspected or diagnosed intraocular tumors / extraocular pathologies and cases presenting with proptosis. Patients lost to follow up and eyes with normal scan were excluded. Supplementary investigation (CT, MRI) done where ever needed. The findings of B-scan then correlated with the ophthalmoscopic/ surgical findings/histology/follow up after treatment. Results: Distinction between intra and extra-ocular pathologies was 100%. The commonest posterior segment pathology in non traumatic eyes was retinal detachment and in traumatic eye was vitreous haemorrhage with diagnostic accuracy of 98.9% and 97.9% respectively. Retinoblastoma and pseudotumor (15%) were the commonest intra and extraocular mass lesions respectively. Accuracy in localization of foreign bodies and dislocated lens, in diagnosing retinoblastoma, in diagnosis and characterization of thyroid orbitopathy, cavernous hemangioma, tumors, cellulitis, dermoids, cysticercosis and intraorbital cysts was excellent. “Triple wall” sign is typical for intraorbital hydatid cyst. Conclusion: B-mode real time ultrasound using non-dedicated all purpose high frequency transducer provides non-ionizing, cost effective, non-invasive technique with excellent image quality and high accuracy for diagnosis and assessment of posterior segment and extraocular pathologies.